2016
DOI: 10.1016/j.eururo.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Therapy in Men With Prostate Cancer

Abstract: Context The use of testosterone therapy in men with prostate cancer was previously contraindicated, although recent data challenge this axiom. Over the past 2 decades, there has been a dramatic paradigm shift in beliefs, attitude, and treatment of testosterone deficiency in men with prostate cancer. Objective To summarize and analyze current literature regarding the effect of testosterone replacement in men with prostate cancer. Evidence acquisition We conducted a Medline search to identify all publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 66 publications
(94 reference statements)
2
59
0
2
Order By: Relevance
“…These findings are similar to what is seen in literature currently, and are explained by the saturation model proposed by Morgentaler & Traish 18,28 . While our rates of BCR were lower than clinical norms, our trial design doesn’t allow comment on causative factors.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are similar to what is seen in literature currently, and are explained by the saturation model proposed by Morgentaler & Traish 18,28 . While our rates of BCR were lower than clinical norms, our trial design doesn’t allow comment on causative factors.…”
Section: Resultssupporting
confidence: 93%
“…The prostatic androgen receptors become saturated with a serum T concentration of around 240-250 ng/dl (8-8.7 nmol/L) 18 . Below this saturation point, PSA is seen to increase in a linear fashion with increasing testosterone, but the relationship becomes uncoupled after this point 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2016 review concluded that although the data on using TTh in men on AS are limited, preliminary studies show no, or minimal, increased risk compared to the quality of life improvements seen with treatment of hypogonadism (98). Conversely, a 2011 study following 25 men with CaP reported highly variable outcomes after starting TTh.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, a 2011 study following 25 men with CaP reported highly variable outcomes after starting TTh. The authors urged caution in treating these patients and concluded that an international registry to collect more data would be the only way to address whether TTh was safe in men with CaP (98,99). While the preliminary studies of TTh in the setting of AS appear to demonstrate the relatively safety of treating hypogonadism with TTh in this setting, it is important to note that none of these studies were randomized or controlled and that more work must be done before unequivocally determining the safety of such treatment.…”
Section: Methodsmentioning
confidence: 99%